Modes of neutrality in the ECtHR jurisprudence related to religious matters: some critical remarks (Stato, Chiese e pluralismo confessionale, 2018)
SUMMARY: 1. Introduction - 2. The meaning of State neutrality: some conceptual clarifications - 3. State’s neutrality vis-à-vis religious organizations: neutrality as absence of interference - 4. State’s neutrality vis-à-vis public education: neutrality as objectivity - 5. State neutrality vis-à-vis religious symbols in the public sphere: neutrality as exclusion of religion - 6. ‘Reversed’ patters of neutrality: the disruptive effect of Lautsi v. Italy - 7. Concluding remarks: decoding the patterns of State neutrality in the jurisprudence of the ECtHR.ABSTRACT: This contribution discusses the notion of State neutrality in the jurisprudence of the European Court of Human Rights. State neutrality has become increasingly relevant in the rulings of the ECtHR concerning religious freedom, with the Court explicitly resorting to the idea that States should act as neutral and impartial organizers of religious life within their community. Yet, the conception of State neutrality developed by the Court is inconsistent and often gives rise to criticism. By exploring the Court’s main jurisprudence in the context of religious disputes, religious education in public education, and the display of religious symbols in public spaces, this contribution seeks to disentangle the different understandings of neutrality employed by the Court and to critically engage with them.